Morphology and evolution of scopula, pseudoscopula and claw tufts in Mygalomorphae (Araneae) - Pérez-Miles, F.; Guadanucci, J. P.L. [UNESP]; Jurgilas, J. P. [UNESP]; Becco, R.; Perafán, C. (Springer Nature, 2017)
We studied the morphology of scopula, claw tufts and a scopula-like feature (pseudoscopula) of tarsi on representatives of all Mygalomorphae spider families. The pseudoscopula is constituted by groups of non-microtriched conical setae. The taxonomic distribution of all these features was studied and mapped on a recent phylogeny of Mygalomorphae and the association of them with the lifestyles of the spiders was analyzed. Adhesive setae, as well as some other setal types found on ventral tarsi are described and characterized. The adhesive face of setae varied in the orientation in different parts of the tarsi, and this variation is more conspicuous in the spiders which only have claw tufts or scopula. We found an association of adhesive scopulae and claw tufts with burrower/cursorial or thin wafer lid trapdoor mygalomorphs as suggested for free hunter spiders, but we found that the pseudoscopula is associated with males of some trap-door and some weavers mygalomorphs. The presence of pseudoscopula widely extended among Mygalomorphae seems to be ancestral for the infraorder. The setal morphology of pseudoscopula suggests chemosensorial function; sparse chemosensory setae were also found in almost all Mygalomorphae. The morphology, functions and evolution of scopula, claw tufts and pseudoscopula are discussed.
Keywords: Copulation; Locomotion; Mygalomorph; Prey-capture; Setae-morphology